Disability-Competent Health Systems - Palsbo, Susan E.; Kailes, June Isaacson (Disability Studies Quarterly, 2006)
In July 2005, the United States Surgeon General issued a national Call for Action to Improve the Health and Wellness of Persons with Disabilities. This article offers one response. Drawing on the best practices of consumer-driven health programs for people with disabilities, we offer a Disability-Competent Health System model. The model integrates health and social services to maximize opportunities for independent living and person-centered care. This approach is an opportunity for the independent living movement to address health-related issues without subscribing to the medical model.